Teknik Ecoprint, Pengembangan Motif Kain Yang Ramah Lingkungan - Wika Watiningsih (Garina, 2022)
Increasing consumer demand, including in the fashion sector, is directly proportional to the waste generated. Unconsciously, the fashion industry is one of the contributors to global pollution. One of the contributions is with a sustainable fashion. Awareness of environmental sustainability encourages environmentally friendly clothing styles become more popular. Designers are competing to make design collections with sustainable materials, It is the ecoprint fabric motif. Ecoprint means the technique of making motifs on cloth by tracing the leaves and then boiling them. Almost 100% of ecoprint fabrics are made using natural materials that are biodegradable. Creating fabrics with ecoprint motifs requires fabric materials derived from natural fibers, both plant and animal fiber. The dyes used come from nature, including from stems, leaves, flowers, fruit skins which when boiled are able to produce the same colors as chemical substances. The motif from leaves that produce natural colors, arranged in such a way is created kind of motif formation. Experimental methods of various in arranging leaves and flowers will produce unique different styles of motifs. Ecoprint as an alternative to sustainable Indonesian ‘Wastra’ expected will become more popular because of the uniqueness of the motifs, sustainable and the high selling price.